Factors Influencing Turnover Intention in Nurses: A Scoping Review - Assidiqy, Birry; Agustina, Hana Rizmadewi; Yudianto, Kurniawan (Indonesian Journal of Global Health Research, 2024)
Urnover intention in nurses is a serious concern in the health care industry, affecting workforce stability and the quality of services provided to patients. Complex factors such as job satisfaction, work environment, and personal factors have been identified as the main causes of nurses' intention to leave their jobs. Purpose: This study aims to review the factors that influence turnover intention in nurses. Methods: A scoping review study design was used with the Arksey and O'Malley approach. A literature search was carried out through the Scopus, PubMed, and CINAHL databases using relevant keywords. Inclusion and exclusion criteria were established for study selection, and data were extracted using manual tables. Data analysis was carried out descriptively qualitatively with a thematic analysis approach. Results: The literature review showed that there were 8 articles that met the inclusion criteria to be included in the analysis. Factors that influence turnover intention in nurses include internal aspects such as job satisfaction, work stress, and organizational commitment, as well as external factors such as the work environment and social support. Conclusion: By deeply understanding these factors, health organizations can design appropriate intervention strategies to reduce turnover intention, increase nursing workforce retention, and improve the quality of health services provided to patients.